Study on the Influence of Geological Structure on Gas Occurrence and Gas Outburst - Guan, Wenbo (International Journal of Natural Resources and Environmental Studies, 2024)
Gas is a gaseous geological body and a product of geological genesis. The geological structure and the historical evolution of coal bearing strata control the generation conditions of coal-bed gas and the preservation conditions of coal-bed gas subjected to depression, uplift, compression and tension in previous tectonic movements. The geological conditions that control the occurrence of gas disasters determine the state of gas occurrence, gas content, gas pressure, gas emission and the risk of coal and gas outburst in coal seams. There are obvious characteristics of zoning and zoning. Gas occurrence and gas outburst are controlled by various geological factors, and geological structure plays a decisive role in coal and gas outburst. Studying the influence of geological structure on gas occurrence law and gas outburst and mastering gas geological law can achieve the purpose of gas prediction and gas control. This paper discusses the influence of fold, fault and sliding structure on gas occurrence, and discusses the influence of geological structure on gas outburst from three aspects of coal seam gas pressure, in-situ stress and coal body structure. It can provide a basis for the prediction of gas outburst and has important significance for the prevention and control of gas accidents in coal mines.